Atenolol in the Treatment of Essential Hypertension - Piddisi, Christine (1986)
In a large, open-label study of 522 patients diagnosed as essential hypertensives, atenolol was both effective and well tolerated. In 392 patients whose blood pressure was measured at the initial visit and after at least four weeks of atenolol therapy, average reductions of 21 mm Hg and 14 mm Hg, were noted in the systolic and diastolic blood pressure respectively. Forty-three patients stopped taking atenolol because of side-effects. The incidence of CNS side-effects was particularly low, and the drug was well tolerated by diabetic patients. Among eight asthmatics who took atenolol, asthma worsened in two. By virtue of its hydrophilicity, cardioselectivity and long half-life, atenolol appears to be a suitable and well-tolerated beta-blocker in the majority of patients.